2021
DOI: 10.3389/fmed.2021.765447
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Anti-neutrophil Cytoplasmic Antibody-Associated Vasculitis With Acute Renal Failure and Pulmonary Hemorrhage May Occur After COVID-19 Vaccination

Abstract: The rare and severe adverse effects associated with coronavirus disease of 2019 (COVID-19) vaccination have been under-appreciated, resulting in many instances of inappropriate management. We describe the case of an elderly woman who developed anti-neutrophil cytoplasmic antibody-associated vasculitis with pulmonary renal syndrome approximately 3 weeks after the first dose of COVID-19 mRNA vaccination (Moderna). Her nasopharyngeal polymerase chain reaction test for the COVID-19 RNA virus was negative. Gross he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Although MPO-ANCAs are known to be pathogenic (28), disease activity of AAV is not always correlated with MPO-ANCA titers, but rather with MPO-ANCA affinity (29,30). However, after initiating treatment of AAV relapse, the titer of anti-MPO antibody decreased coinciding with improvements in pulmonary hemorrhage (Figure 3), which is similar to a previous case report (31). In addition, Sharma et al reported a unique case demonstrating that diffuse alveolar hemorrhage occurred 8 h after the first dose of COVID-19 mRNA vaccination without any evidence of immunological complications such as elevation of anti-MPO antibody titers (32).…”
Section: Discussionsupporting
confidence: 83%
“…Although MPO-ANCAs are known to be pathogenic (28), disease activity of AAV is not always correlated with MPO-ANCA titers, but rather with MPO-ANCA affinity (29,30). However, after initiating treatment of AAV relapse, the titer of anti-MPO antibody decreased coinciding with improvements in pulmonary hemorrhage (Figure 3), which is similar to a previous case report (31). In addition, Sharma et al reported a unique case demonstrating that diffuse alveolar hemorrhage occurred 8 h after the first dose of COVID-19 mRNA vaccination without any evidence of immunological complications such as elevation of anti-MPO antibody titers (32).…”
Section: Discussionsupporting
confidence: 83%
“…As a result of the new onset ANCA vasculitis, one patient became dependent on dialysis (196), while in the other case renal improvement was achieved after plasma exchange, pulse steroid and cyclophosphamide therapy (197). Additional case of ANCA vasculitis which manifested as renal failure together with pulmonary hemorrhage 3 weeks after the first dose of mRNA-1273 was also described (198).…”
Section: Vasculitismentioning
confidence: 99%
“…Whether or not AAV is induced by COVID-19 vaccination remains unclear; in this regard, we propose a connection between the vaccine and AAV. Recently, Asian reports of AAV after COVID-19 vaccination have been increasing in Japan, Taiwan, Nepal, and India (27)(28)(29)(30)(31)(32). Because a third dose of the COVID-19 vaccine has been rolled out, clinicians should be aware of the possibility of new-onset AAV.…”
Section: Discussionmentioning
confidence: 99%